Recife, City of People? A study based on the archeology of Foucault (Desenvolvimento em Questão, 2020)
This article aims at analyzing the discourse involved in the city council program called “Recife, city of the people”, from Foucault's archeology of knowledge perspective. The corpus of this research consists of six videos available on the Facebook® page of the city council of Recife in 2014, when government agency released the slogan "Recife, Cidade das Pessoas”. The study is justified by the need of understanding how the political discourses are spread and how these discourses have no explicit assumptions. We believe that a better design of the influence of discourses, along with further clarification of social significance exercised by them, can contribute to a more democratic social life, which will be accessible to the entire population. For the present study, no theory was previously defined. The option for this construction enables the non-interference of external factors guiding the analyses. Data was analyzed without theoretical influences, so that the theoretical constructs emerged from the analysis rather than the reverse. However, the vision of authorship in relation to the concept of speech interferes with the analysis and serves as a theoretical lens through which data will be displayed. For results, two discursive formations were found: (1) the protection of the Government and (2) healthy lifestyles practices, with includes social, cultural and physical. This discursive formation is founded on the pillars of bio-politics and sustainability, quality of life and social change. It was noticed that the program has a goal it is to influence people's opinions about public spaces and mobility in a municipality.